Avaliação anti-inflamatória do alcaloide sintético inédito tetrahidroisoquinolínico 2-(7-metoxi-1,2,3,4-tetrahidroisoquinolina-1-il) fenol (MTF) em modelos murinos de inflamação aguda - Oliveira, João Batista de (2023)
Inflammation is a physiological response of the body to maintain tissue homeostasis in the face of harmful stimuli. Acute lung injury (ALI), an inflammatory condition that precedes acute respiratory distress syndrome (ARDS), has gained evidence in patients with COVID-19 because the accumulation of neutrophils and pro-inflammatory cytokines in the lungs, promoting pulmonary dysfunction. So far, there is no standard pharmacotherapy for this pathology, and numerous studies are aimed at elucidating new drugs with anti-inflammatory potential. Thus, the synthetic alkaloid 2-(7-methoxy1,2,3,4-tetrahydroisoquinolin-1-yl) phenol (MTF) appears as a promising molecule to add to the therapeutic arsenal of anti-inflammatory drugs. Therefore, the objective of this work was to evaluate the anti-inflammatory effect of MTF in murine models of ALI, peritonitis and paw edema. In the experimental model of ALI, male BALB/c mice were challenged, by nasal instillation, with lipopolysaccharide (LPS) and, one hour later, they were orally treated with MTF (1.25 mg/kg, 2.5 mg/kg or 5 mg/kg) and, 24 hours later, bronchoalveolar lavage fluid (BALF), serum and lungs were collected. Treatment with MTF (2.5 mg/kg) reduced neutrophil migration, independent of lymphocytes and macrophages in BALF and decreased production of TNF-α, IL-1β and IL-6 in BALF and serum. It reduced the formation of pulmonary edema and attenuated histopathological changes, such as edema, cellular infiltrate and hemorrhage. For the paw edema model, female Swiss mice were pre-treated with MTF (2.5 mg/kg) and challenged, intraplantar, with the phlogistic agents carrageenan, prostaglandin (PGE2), bradykinin (BK), serotonin ( 5-HT), compound 48/80 or histamine and, for the peritonitis model, the animals were challenged intraperitoneally with carrageenan (1%). Pre-treatment with MTF reduced paw edema induced by phlogistic agents and, in the peritoneum, there was a decrease in the migration of neutrophils and mononuclear cells, in vascular permeability and in the cytokines TNF-α, IL-1β and IL6. In addition, in silico analyzes showed that MTF has good oral bioavailability, with low theoretical toxicity, and that the anti-inflammatory effects of the molecule may be associated with the inhibition of the TLR4/MAPK-p38 signaling pathway. Therefore, the results presented in this work demonstrate the anti-inflammatory potential of MTF, placing it as a promising molecule in the development of a drug that adds to the antiinflammatory therapeutic arsenal.